Evaluation of Power Minimization for Routing Protocol and Multicast Networks - Shabir Ahmed mir; T Padma (Institute of Advanced Engineering and Science, 2018)
In this paper explore the scenario of wireless multicast with a single source and multiple relay that together convey consecutively refined sources to multiple receiver. Joint source-channel coding (JSCC) protocol is proposed aimed at mitigating the complexity and difficulty in signal synchronization in multicast taking end-to-end mean cube error deformation as the quality of service measure the problems of JSCC communication are formulated to minimize the total power utilization where both relay selection and power allocation at the base station (BS) and all the relays are jointly determined to solve the formulated problem that is nonetheless nonlinear in nature a two-step iterative algorithm is investigated for power allocations at all transmitters where a in order quadratic programming method is developed into find a strict local minimum. To reduce the computation complexity a heuristic algorithm for relay selection is presented. Case studies are conducted to verify the proposed formulations and solution methods.